The complete chloroplast genome sequence of a Bolivian wild chili pepper, Capsicum eximium Hunz. (Solanaceae) - Raveendar Sebastin; Kyung Jun Lee; Gyu-Taek Cho; Myoung-Jae Shin; Seong-Hoon Kim; Do Yoon Hyun; Jung-Ro Lee (Mitochondrial DNA. Part B. Resources, 2019)
Bolivia is believed to be the origin of the Capsicum eximium, a wild chilli pepper. In this study, we sequenced the complete chloroplast (cp) genome sequence of C. eximium to investigate its phylogenetic relationship in the family Solanaceae. The complete cp genome sequence is 156,947 bp in length with 37.7% overall GC content and exhibits a typical quadripartite structure comprising one pair of inverted repeats (25,847 bp) separated by a small single-copy region (17,912 bp) and a large single-copy region (87,341 bp). The cp genome contains 113 unique genes, including 79 protein coding genes, 30 tRNA genes, and 4 rRNA genes. Of these, 21 genes are duplicated in the inverted repeat regions. The phylogenetic analysis indicated C. eximium is clustered in the Capsicum clade.